Use of Chitosan to Control Vibrio harveyi Infection on White Shrimp Litopeneaus vannamei - Sukenda, .; Tri Anggoro, Y.; Wahjuningrum, D.; Rahman, . (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
Immunostimulation and antibacterial effect of chitosan against vibriosis were examined in white shrimp (Litopenaeus vannamei). Control shrimps were injected with 0.05 μl of sterile sea water, while experimental shrimps were injected with 2, 4 and 6 μg per g shrimp of chitosan. All shrimps were subsequently challenged by 106 CFU/ml of live Vibrio harveyi by injection method. Survival rate of shrimps injected with chitosan were found to slightly increase in accordance with dose of chitosan, even not statistically significant. Total haemocyte count and phagocytic index at experimental shrimps were over than control shrimps up to three days post injection. Number of V. harveyi in the intestine of experimental shrimps were lower than control shrimps indicates an antibacterial activity of chitosan to combat infection. Keywords: chitosan, Vibrio harveyi, haemocyte, phagocytic index, Litopenaeus vannamei ABSTRAK Efek imunostimulasi dan antibakterial dari kitosan melawan vibriosis dilihat pada udang putih (Litopenaeus vannamei). Udang control disuntik dengan 0,05 μl air laut steril, sedangkan udang uji disuntik dengan kitosan 2, 4 dan 6 μg per g udang. Semua udang diuji tantang dengan 106 CFU/ml bakteri Vibrio harveyi hidup dengan metode penyuntikan. Sintasan udang yang disuntik dengan kitosan meningkat berbarengan dengan peningkatan dosis kitosan, meskipun tidak menunjukkan perbedaan yang nyata. Jumlah total hemosit dan indeks fagositosis pada udang lebih tinggi dibandingkan kontrol sampai tiga hari pasca penyuntikan. Jumlah V. harveyi dalam saluran pencernaan dari udang uji lebih rendah dibandingkan udang kontrol, hal ini menunjukkan aktifitas antibacterial dari kitosan dalam melawan infeksi. Kata kunci: kitosan, Vibrio harveyi, hemosit, indeks fagositosis, Litopenaeus vannamei